Control interno del área de tesorería de la Compañía FERRETONSA S.A y su impacto en la liquidez de sus estados financieros - Manzo Peñafiel, Ámbar Sherydan (2024)
FERRETONSA SA is a company that was established approximately 13 years ago and that as its main economic activity is dedicated to the wholesale of hardware and locks: hammers, saws, screwdrivers, and other hand tools, accessories, and devices. Since its creation, the company has gained renown in the work environment due to the quality of its products offered to its clientele, it can be said that at a professional level the company is on the right path and also close to expansion; but there are certain difficulties in the same, including deficiencies specifically in the treasury area which has created many problems in the management of the financial statements of the company, since they do not have an adequate internal control system............